Activation Dynamics and Immunoglobulin Evolution of Pre-existing and Newly Generated Human Memory B cell Responses to Influenza Hemagglutinin - Andrews, Sarah F.; Chambers, Michael J.; Schramm, Chaim A.; Plyler, Jason; Raab, Julie E.; Kanekiyo, Masaru; Gillespie, Rebecca A.; Ransier, Amy; Darko, Sam; Hu, Jianfei; Chen, Xuejun; Yassine, Hadi M.; et al. (Immunity (Cambridge, Mass.), 2019)
Vaccine-induced memory B cell responses to evolving viruses like influenza A involve activation of pre-existing immunity and generation of new responses. To define the contribution of these two types of responses, we analyzed the response to H7N9 vaccination in H7N9-naive adults. We performed comprehensive comparisons at the single-cell level of the kinetics, Ig repertoire, and activation phenotype of established pre-existing memory B cells recognizing conserved epitopes and the newly generated memory B cells directed toward H7 strain-specific epitopes. The recall response to conserved epitopes on H7 HA involved a transient expansion of memory B cells with little observed adaptation. However, the B cell response to newly encountered epitopes was phenotypically distinct and generated a sustained memory population that evolved and affinity matured months after vaccination. These findings establish clear differences between newly generated and pre-existing memory B cells, highlighting the challenges in achieving long-lasting, broad protection against an ever-evolving virus. [Display omitted] •Newly generated memory B cells evolve and affinity mature over several months•Long-term pre-existing memory B cells evolve little upon re-vaccination•Newly generated memory B cells transiently become atypical, T-bethi CD21lo CD27−•T-betlo CD21hi CD27−, but not CD27+, resting memory B cells are maintained long-term Influenza vaccination occurs in the context of pre-existing immunity. Andrews et al. compare the pre-existing memory IgG B cell response recognizing conserved epitopes on influenza hemagglutinin with the newly generated response to strain-specific epitopes upon H7N9 vaccination. The differences in magnitude, phenotype, and affinity maturation between the two responses highlight the challenges in achieving long-lasting, broad protection against an ever-evolving virus.